The Concept of Islamic Education According to Ibn Sina and Ibn Khaldun - Fatkhur Roji; Ibrahim El Husarri (Nazhruna: Jurnal Pendidikan Islam, 2021)
This study aims to analyze the similarities and differences in the views of Ibn Sina and Ibn Khaldun in the concept of Islamic education. The research approach is a qualitative type of literature. The data source of this research is literature in the field of Islamic education, especially about the Muqoddimah and As-Sifa 'books and other related literature. Data collection techniques are carried out by tracing related references, both manually and digitally. The collected data is then displayed, reduced and constructed into a new, complete and stressful concept. Data analysis was performed using content analysis that prioritizes intertextuality and meaning creativity. The results showed that the similarities between Ibn Sina and Ibn Khaldun, which lie in the objectives of Islamic education, together form a good human being, educators or teachers must have everything in order to know the methods, techniques, science that suit the needs of students, and in science, both agree that science must be in accordance with its use so that knowledge is not in vain. Whereas in terms of the difference covering the curriculum, the eye of Ibn Sina and Ibn Khaldun's Equation, lies in the goal of Islamic education, together forming a human being, educators or teachers must have everything in order to know the methods, techniques, knowledge that suit the needs of students, and scientific, both agree that science must be in accordance with its use so that knowledge is not in vain.